Implementasi Pojok Literasi Teknologi untuk Meningkatkan Keterampilan Digital di Desa Dersalam - M. Alexander Zulfikar; Afif Rizkyan Syah; Zayyan Cahya Ramadhan; Ruth Natalia Susanti (Jurnal Pengabdian Masyarakat Nusantara, 2024)
The low level of literacy in the digital era is one of the main challenges facing Indonesia including in Dersalam Village, Kudus Regency, Central Java. Digital literacy, containing the ability to access, manage, and evaluate sources of information is essential for boosting productivity in people’s lives. PPK Ormawa program from Universitas Muria Kudus took place in Dersalam Village aiming to improve digital literacy among the community by establishing five Reading Corners, Technology Reading Corner is one of it. This program is implemented within three stages: observation, setting up the spot, and conducting educational activities from August to November 2024. At the Technology Reading Corner, People are trained to use Microsoft Office, and are introduced to future technologies such as Artificial Intelligence (AI). The results indicate an increase in the community’s learning interest and digital skills, particularly in operating technological devices to support their daily activities and even their entrepreneurship. Through this initiative, there is a strong hope that Dersalam can become one of a smart village, more adaptive to technological advancements, by enhancing the digital literacy of their people as a first step toward sustainable social transformation.